1994
DOI: 10.1164/ajrccm.149.6.8004326
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux with nasogastric tubes. Effect of nasogastric tube size.

Abstract: Pulmonary aspiration of gastric contents results initially from reflux of stomach contents into the esophagus. Small-bore enteral feeding tubes are thought to result in less pulmonary aspiration and less reflux. We prospectively investigated the effect of nasogastric tube size upon gastroesophageal (GE) reflux in normal volunteers in a randomized crossover trial. Reflux was assessed by gastroesophageal scintiscanning, a radioisotopic technique that detects and quantitates GE reflux. A total of 11 subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
3
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 6 publications
2
22
3
1
Order By: Relevance
“…The lack of significant association between reflux and aspiration pneumonia is in disagreement with other studies that found a strong association between reflux and pneumonia [18,[35][36][37][38][39][40][41][42]. However, these studies suggest that GE reflux is most dangerous in persons who are in the intensive care unit or in postsurgical units, two groups that we did not recruit.…”
Section: Variables Significantly Associated With Aspiration Pneumoniacontrasting
confidence: 93%
See 1 more Smart Citation
“…The lack of significant association between reflux and aspiration pneumonia is in disagreement with other studies that found a strong association between reflux and pneumonia [18,[35][36][37][38][39][40][41][42]. However, these studies suggest that GE reflux is most dangerous in persons who are in the intensive care unit or in postsurgical units, two groups that we did not recruit.…”
Section: Variables Significantly Associated With Aspiration Pneumoniacontrasting
confidence: 93%
“…In fact, several studies of tube-fed patients who are taking no food or liquid by mouth have shown that tube feeding is associated with a higher rate of pneumonia than in patients who are eating [19,23,28,30,31,33,34]. A large body of literature has focused on the association between gastroesophageal reflux and aspiration [18,[35][36][37][38][39][40][41][42]. In clinical settings, ''aspiration precautions'' such as elevating the head of the bed are commonly carried out to prevent aspiration of refluxed material.…”
mentioning
confidence: 99%
“…A fourth possible mechanism would be a relationship between nasogastric tube syndrome and gastroesophageal reflux [9] due to decreased swallow reflex, decreased level of consciousness, supine position of the patient and presence of the tube across cardioesophageal junction.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment is based in esophageal dilations with aid of digestive endoscopy 3,10,14,22 . Was used Savary-Gilliard dilators, and surgical treatment was indicated for 61.5% of cases with satisfactory results, early and late.…”
mentioning
confidence: 99%